Pelatihan Massage Olahraga Sebagai Teknik Relaksasi Dan Pemulihan Otot Bagi Masyarakat Di Desa Blitar Kabupaten Rejang Lebong - Sumantri, Ajis; Saputra, Roni; Andresta, Yulva; Dewa, Barata Harsena (Jurnal Dehasen Untuk Negeri, 2025)
The community service activity titled "Sports Massage Training as a Technique for Relaxation and Muscle Recovery for the Community in Belitar Village" aims to provide education and practical skills to the community in maintaining muscle health through proper massage techniques. The training involved 30 participants from various backgrounds who actively attended two main sessions: theory and practice. The theory session provided an understanding of the benefits of sports massage, such as improving blood circulation, reducing muscle tension, and accelerating body recovery. Meanwhile, the practice session focused on mastering basic massage techniques that could be applied independently. The results of the activity showed very positive responses from the participants. Most participants stated that the training was relevant to their needs and offered tangible benefits for daily life. However, several challenges were encountered, such as the limited availability of teaching aids and the need to simplify theoretical materials to facilitate understanding. Recommendations for future activities include improving facilities, extending the duration of training, and developing more specific training themes. Overall, this activity successfully achieved its stated objectives and is expected to have a sustainable impact on the community of Belitar Village. It also strengthens the role of Universitas Dehasen Bengkulu in supporting community empowerment through relevant and practical service programs.